Estimation of Yield Surface on Iron Powder Compaction for Finite Element Analysis using Drucker-Prager Cap Model. (March 2019) - Ogawa, R; Yoshimura, T; Yagi, N; Mizuta, K; Taniguchi, Y
Abstract: Shear failure yield line in Drucker-Prager yield surface for conventional atomized iron powder has been estimated with critical stress state and uniaxial failure stress state by single shear test and uniaxial failure test for green compact. Lateral force measurement test was also conducted using newly devised instrumented die compaction system to identify compaction yield characteristics as Cap yield surface. By those estimations, materials input parameters for Drucker-Prager Cap model have been determined successfully. Finite element analysis of simple closed-die compaction has been conducted and good correspondence in variation of compaction pressure with densification has been recognized.